PENGARUH PROFITABILITY DAN FIRM SIZE TERHADAP FIRM VALUE DENGAN MEDIASI CAPITAL STRUCTURE - Valencia, Hilary Larissa; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to obtain empirical evidence regarding the effect of profitability and firm size on firm value with capital structure as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. This study used 73 manufacturing companies as samples after being selected by purposive sampling method. Data processing in this study used EViews 12 SV software and hypothesis testing was carried out using multiple regression analysis. The results of this study indicate that profitability and firm size have significant positive effect on capital structure, profitability and capital structure have significant positive effect on firm value, firm size has significant negative effect on firm value, capital structure cannot mediate the effect of profitability on firm value. Meanwhile the capital structure can mediate the effect of firm size on firm value.